Decreased expression levels of PIWIL1, PIWIL2, and PIWIL4 are associated with worse survival in renal cell carcinoma patients - Iliev, Robert (Onco Targets Ther, 2016)
Piwi-interacting RNAs (piRNAs) are a newly discovered class of small non-coding RNAs involved in silencing of transposable elements and in sequence-specific chromatin modifications. PIWI proteins (PIWIL), which belong to the family of Argonaute genes/proteins, bind to piRNAs and function mainly in germ line cells, but more recently were described to be functional also in stem cells and cancer cells. To date, there have been four PIWI proteins discovered in humans: PIWIL1, PIWIL2, PIWIL3, and PIWIL4. Recent studies suggested that deregulated expression of PIWI proteins and selected piRNAs is common to many types of cancers. We found significantly lower expression of PIWIL1 (P<0.0001) and piR-823 (P=0.0001) in tumor tissue in comparison to paired renal parenchyma. Further, we observed a progressive decrease in PIWIL1 (P=0.0228), PIWIL2 (P=0.0015), and PIWIL4 (P=0.0028) expression levels together with increasing clinical stage. PIWIL2 (P=0.0073) and PIWIL4 (P=0.0001) expression also progressively decreased with increasing Fuhrman grade. Most importantly, low-expression levels of PIWIL1 (P=0.009), PIWIL2 (P<0.0001), and PIWIL4 (P=0.0065) were significantly associated with worse overall survival in renal cell carcinoma (RCC) patients. Our results suggest the involvement of PIWIL genes and piR-823 in RCC pathogenesis, and indicate PIWIL1, PIWIL2, and PIWIL4 as potential prognostic biomarkers in patients with RCC.